Development of psoriasis in IBD patients under TNF-antagonist therapy is associated neither with anti-TNF-antagonist antibodies nor trough levels. (1st December 2016) - Protic, Marijana; Schoepfer, Alain; Yawalkar, Nikhil; Vavricka, Stephan; Seibold, Frank
Abstract: Background: The cause of anti-TNF-induced psoriasis is still unknown. Objective: We aimed to evaluate if the appearance of psoriasis under anti-TNF therapy is associated with anti-TNF antibody levels and TNF-antagonist trough levels. Methods: In this case-control study we identified 23 patients (21 with Crohn's disease [CD], two with ulcerative colitis [UC]) who developed psoriasis under infliximab (IFX, n  = 20), adalimumab (ADA, n  = 2), and certolizumab pegol (CZP, n = 1) and compared them regarding the anti-TNF-antagonist antibody levels with 85 IBD patients (72 with CD, 13 with UC) on anti-TNF therapy without psoriasis. Results: Median disease duration was not different between the two groups (7 years in the group with psoriasis under TNF-antagonists vs. 10 years in the control group, p  = 0.072). No patient from the psoriasis group had antibodies against TNF-antagonists compared to 10.6% in the control group ( p  = 0.103). No difference was found in IFX trough levels in the group of patients with psoriasis compared to the control group (2.6 μg/mL [IQR 0.9–5.5] vs. 3.4 μg/mL [IQR 1.4–8.1], p  = 0.573). TNF-antagonist therapy could be continued in 91.3% of patients with TNF-antagonist related psoriasis and most patients responded to topical therapies. Conclusion: Anti-TNF-induced psoriasis seems to be independent of anti-TNF antibodies and trough levels. Interruption of Anti-TNF therapy is rarely necessary.